Preoperative Differences in Intracranial Facial Versus Vestibular Schwannomas: A Four Nerve Assessment. (20th May 2021) - Erbele, Isaac D.; Klumpp, Micah L.; Arriaga, Moisés A.
Abstract : Objectives: Assesses whether preoperative functional testing can distinguish vestibular schwannomas from facial nerve schwannomas medial to the labyrinthine segment. Study Design: Retrospective cohort. Methods: Retrospectively review surgically managed intracranial facial and vestibular schwannomas between January 2015 and December 2019 at two tertiary care centers. Patients with neurofibromatosis 2 and surgery for recurrence were excluded. Preoperative functional testing to include House‐Brackmann scores, electroneuronography (ENoG), cervical vestibular evoked myogenic potentials (cVEMP), caloric testing, acoustic brainstem responses (ABRs), acoustic reflexes, and audiograms was compared between the two groups of schwannomas. Results: Twelve facial and 128 vestibular schwannomas met inclusion criteria. In only one case was a facial schwannoma diagnosed preoperatively from imaging. No statistically significant difference was found in preoperative House‐Brackmann scores, ENoG, cVEMP, caloric testing, ABRs, or acoustic reflexes. Pure tone average was worse in the vestibular schwannoma group (63 dB [95% CI: 58–68 dB] vs. 46 dB [95% CI: 34–58 dB], P  = .01), and the difference was more apparent in the lower frequencies. Word recognition score was better in the facial schwannoma group (66% [95% CI: 45–86%] vs. 41% [95% CI: 34–47%], P  = .02). Conclusion: Specialized preoperative functional evaluation of the nerves of the internal auditory canal cannot reliably predict the presence of an intracranial facial schwannoma. Hearing is better in facial schwannomas, particularly in the lower frequencies. This should raise the index of suspicion for an intracranial facial schwannoma, especially in candidates for hearing preservation vestibular schwannoma surgery. Level of Evidence: 3 Laryngoscope, 131:2098–2105, 2021